(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The growing resistance of pathogenic microorganisms to synthetic drugs has increased interest in plant-derived antimicrobial agents. Aquatic plants, known for their ecological and medicinal significance, are being investigated as potential sources of bioactive compounds. Azolla pinnata, a fast-growing aquatic fern, is traditionally used in agriculture due to its nitrogen-fixing ability. Recent phytochemical studies have highlighted its potential antibacterial and antifungal properties, attributed to compounds such as flavonoids, alkaloids, saponins, and tannins. However, systematic studies on its microbial inhibition spectrum remain limited. Although Azolla is known to contain several biologically active substances, little is known about the comparative effectiveness of different extraction methods and their specific actions against common pathogenic microbes. This study aimed to assess the phytochemical composition of Azolla pinnata extracts and evaluate their antibacterial and antifungal activity against selected pathogens using ethanol, methanol, and water-based extractions. The phytochemical analysis confirmed the presence of flavonoids, phenolics, alkaloids, and saponins. Ethanol extracts demonstrated superior antibacterial activity against Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa, while also showing significant antifungal effects against Candida albicans and Aspergillus niger. The mechanisms included membrane disruption and inhibition of protein synthesis. This is one of the first studies to comparatively evaluate solvent-dependent antimicrobial properties of Azolla pinnata, suggesting its efficacy as a natural bioactive source. The findings suggest Azolla pinnata as a promising candidate for developing plant-based antimicrobial agents in pharmaceutical, agricultural, and environmental biotechnolo gy fields.